Elasticity of Agricultural Prices in Russia: An Empirical Study of Energy and Monetary Channels - Burakov, Dmitry (International Journal of Energy Economics and Policy, 2016)
In this paper, we investigate long and short-term direct and indirect impact of changes in oil prices (including shocks to exchange rate) and bank lending policy (interest rate channel) on prices of six groups of agricultural products in Russia (buckwheat, potatoes, oat, wheat, rye, barley). In this paper, Granger causality approach is applied to test long-run interlinkages with monthly data from January 1999 to October 2015. For testing the response of agricultural prices to sudden shocks in oil prices, exchange rate and interest rates for agricultural loans in the short run, we use impulse-response techniques. The results of impulse response analysis show that agricultural prices are not particularly sensitive to changes in oil prices, exchange rate of Russian ruble and banks' interest rates in short run, except for imported and not subsidized commodities. In the long run, Granger causal relationship test shows same results. Keywords: agricultural commodity, world oil prices, exchange rate, interest rate, Granger causality test, impulse response analysis. JEL Classifications: F31, Q1